2006
DOI: 10.1002/chin.200648207
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Investigation of the Flowers of Punica granatum.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…PGF has been reported for the management of diabetes in Unani and Chinese medicine (Ali & Sharma 2006). It was confirmed, previously, that most of compounds (actitannins) isolated from the crude extract of P. granatum showed a non-specific enzyme inhibition in vitro except EA which has a specific a-glucosidase inhibition (Li et al 2014).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…PGF has been reported for the management of diabetes in Unani and Chinese medicine (Ali & Sharma 2006). It was confirmed, previously, that most of compounds (actitannins) isolated from the crude extract of P. granatum showed a non-specific enzyme inhibition in vitro except EA which has a specific a-glucosidase inhibition (Li et al 2014).…”
Section: Resultsmentioning
confidence: 77%
“…Isolation of antidiabetic principles from the fruit rinds of P. granatum was also reported (Jain et al 2012). Its flowering part has been recommended in Unani literature as a remedy for diabetes (Ali & Sharma 2006). The methanol extract (PGFMe) of P. granatum flowers demonstrated a potent inhibitory effect on a-glucosidase and improved postprandial hyperglycemia in type 2 diabetes (Li et al 2005).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…15 17 The anti-inflammatory effect of pomegranate may be attributed to its considerable immune regulatory activity over macrophage and T and B lymphocyte subsets (Ross et al). 4 In vivo study conducted by Grindwit et al in 2003 18 tested the effects of combined extracts from Centella asiatica, commonly known as Asiatic pennywort, and Pomegranate pericap on periodontal wound healing following scaling and root planing. The placement was done subgingivally after scaling and root planing.…”
Section: Pomegranate Mouthrinsementioning
confidence: 99%
“…The powdered flower buds are being used in bronchitis (Ross et al 2001). 3 Flower juice is recommended as a gargle for sore throat, in leukorrhea, hemorrhages and ulcers of the uterus and rectum (Ali et al 2006). 4 The root bark and stem bark of the plant are used as an astringent and anthelmintic specification against tapeworms.…”
Section: Introductionmentioning
confidence: 99%
“…Flowers of the P. granatum contains different tannins such as ellagic acid and gallic acid, [27] 1, 2-di-O-galloyl-4, 6-O-(S)hexahydroxydiphenyl b-D-glucopyranoside, pomegranatate [28] as well as different flavonoids such as apigenin, punicaflavone etc. [29] Besides, the flower also contains different triterpenoids: ursolic acid, maslinic acid and asiatic acid. [30] The observed antihyperlipidemic activity of the flower extract of Punica granatum may be due to the presence of the above mentioned flavonoids, tannins and triterpenoids as previously it has been reported that flavonoids [31] , tannins [8] and terpenoids [32] possess antihyperlipidemic activity.…”
Section: Biochemical Estimations Of Lipid Profilementioning
confidence: 99%